Rare presentation of multisystem inflammatory syndrome in an adult associated with SARS-CoV-2 infection: unilateral neck swelling. Issue 5 (12th May 2021) - Li, Mozhu; Haque, Waqas; Vuppala, Suchith; Tobias, Ethan
Abstract : Multisystem inflammatory syndrome in adults (MIS-A) is a rare but often severe complication of SARS-CoV-2 infection. While several case reports about MIS-A in the setting of COVID-19 have been published since the term was first coined in June 2020, a clear description of the underlying pathophysiology and guideline-based recommendations on the diagnostic and therapeutic approach are lacking. What has been reported is that in the absence of severe respiratory illness, MIS-A can present with hypotension or shock, high-grade fever, abdominal pain, diarrhoea and severe weakness days to weeks after SARS-CoV-2 infection. Here, we present a case of a 28-year-old man who presented with a rarely described initial symptom: unilateral neck swelling. His presentation, disease progression and treatment course provide further information about MIS-A as a complication and in formulating diagnostic guidelines.